Makna Ghuluw dalam Islam: Benih Ekstremisme Beragama - Sihabuddin Afroni (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
This article explore the concept of ghuluw in Islam, as a seed of extremism in the name of religion. This article trace the term ghuluw in Islamic history and how Islam (through the Qur’an and Hadith) discuss this term. Etymologically, the term ghuluw means exaggerating about something. Terminologically, ghuluw means the model of excessive understanding of religious teaching deviated from its orininal meaning. Several attitudes categorized as ghuluw include: fanatic, prejudice, and blame; and even accusing of infidelity. Islam condemns all those characteristics as explain in the Qur’an and Sunna. Islam is a religion that promotes honour, peace, harmony and balance. Currently in Indonesia, however, there are two contrasting Islamic groups: on one side there has been increasing number of people who can be labeled as extremist, violent, and literalist. In another side, there is an Islamic group who tends to ignore the main principles of Islam. These two Islamic groups spread widely in Indonesian Islamic society.